2017
DOI: 10.1159/000464430
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of MicroRNA-146a/Notch2 Signaling Regulating IL-6 in Graves Ophthalmopathy

Abstract: Background/Aims: We intended to investigate the significance of microRNA-146a, Notch2 and IL-6 on Graves ophthalmopathy (GO) and the relationships among them. Methods: About 27 GO patients were incorporated in this study, including 13 patients with inactive GO and14 patients with active GO. Another 15 patients who had previously received strabismus orthopedics or ophthalmectomy due to trauma were selected as the control population. QRT-PCR assay was used to detect microRNA-146a and Notch2 expression levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
3
12
0
1
Order By: Relevance
“…However, the role played by miR-146a in GO may be a little more complex. In contrast to the results of our previous study, Wang et al 30 reported that miR-146a exerted a pro-inflammatory effect (thus increasing IL-6 production), inhibiting the miR-146a target gene notch2, leading to exacerbation of GO, which is consistent with the findings of our previous study 30. Wei et al 31 reported that the circulating miR-146a level was significantly decreased in GO compared with non-GO subjects.…”
Section: Discussionsupporting
confidence: 88%
“…However, the role played by miR-146a in GO may be a little more complex. In contrast to the results of our previous study, Wang et al 30 reported that miR-146a exerted a pro-inflammatory effect (thus increasing IL-6 production), inhibiting the miR-146a target gene notch2, leading to exacerbation of GO, which is consistent with the findings of our previous study 30. Wei et al 31 reported that the circulating miR-146a level was significantly decreased in GO compared with non-GO subjects.…”
Section: Discussionsupporting
confidence: 88%
“…Overexpression of miR-146a induced repression of Numb and an increase in Notch-1 expression level, which is in agreement with earlier verified miR-146a direct target studies [ 63 , 64 , 65 ]. This treatment decreased Notch-2 expression level, which is also in agreement with previous data [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…miR-146a is an important regulator of many cellular functions and targets different genes in different cell types [ 40 , 41 , 42 ]. It plays a major role in several diseases, such as diabetes [ 40 ], cancer [ 41 ], and Graves ophthalmopathy [ 42 ], and its association with different pathways suggests its involvement in cell migration [ 9 , 10 , 43 ], invasion [ 44 ], differentiation [ 45 ], and proliferation [ 44 ]. Our previous studies also revealed that miR-146a plays a regulatory role in corneal wound healing and limbal epithelial stem cell maintenance in normal and diabetic corneas [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that miR-146a participated in several types of autoimmune diseases, including rheumatoid arthritis (17). In a previous report, miR-146a has been revealed to reduce the pathogenesis of GO via exerting anti-inflammatory and anti-fibrotic effects (11), while another study demonstrated that the upregulation of miR-146a promoted inflammation and disease progression (20). These studies have indicated that the effect of miR-146a on GO may be complex, as miR-146a may exert distinct functions in different cell types or interact with various target mRNAs.…”
Section: Discussionmentioning
confidence: 97%
“…miR-146a has been reported to serve a role in a variety of autoimmune diseases, including rheumatoid arthritis, systemic lupus erythematosus and osteoarthritis (19). Previous studies have indicated that miR-146a regulated the expression of inflammatory factors in GO orbital fibroblasts (19,20). The current study aimed to investigate the effect of miR-146a on the production of HA and collagen I in GO orbital fibroblasts, and indicated that miR-146a may be used as a novel target for the treatment of GO.…”
Section: Introductionmentioning
confidence: 99%